Performance, adsorption and kinetic study of AgY zeolite for DBT desulfurization - Saeed, Radhaa; Naife, Tariq M.; Kadhim, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This study focuses on preparing and evaluating AgY zeolite as an adsorbent for the desulfurization (ADS) of dibenzothiophene (DBT) using a model fuel. Kinetic models and adsorption isotherms were investigated for this process. The AgY zeolite characterization was studied using XRD, BET, and XRF. XRD and XRF techniques revealed that AgY zeolite was successfully prepared with 21.42% wt. Ag. The BET results showed that the pore volume of AgY zeolite was 0.3596 cm³/g and the surface area was 531 m²/g. The desulfurization study was done with an initial sulfur content of 100–460 ppm. With 93% sulfur removal from the initial concentration of 100 ppm, ultra-deep desulfurization was achieved. The effect of contact time on the adsorption efficiency was investigated within a range of 10-120 min, and the results showed that most sulfur removal (52%) occurred after 10 minutes, while it reached 75% after 120 min with a sulfur capacity of 57.5 mg S/g. The results indicated that the Langmuir isotherm model was the most suitable to describe the process with R² of 99.29%, while the pseudo-second-order was the most fitted kinetic model to the data with R² of 98.57%.